2019
DOI: 10.1096/fj.201901333r
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the aryl hydrocarbon receptor accelerates aging in mice

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand‐activated transcription factor, largely known for its role in xenobiotic metabolism and detoxification as well as its crucial role as a regulator of inflammation. Here, we have compared a cohort wild‐type and AhR‐null mice along aging to study the relationship between this receptor and age‐associated inflammation, termed as “inflammaging,” both at a systemic and the CNS level. Our results show that AhR deficiency is associated with a premature aged phenotype, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 47 publications
(71 reference statements)
0
33
0
Order By: Relevance
“…It is discussed that AhR activation induces oxidative stress as a result of excessive generation of ROS. Recent studies indicate that AhR also affects several age-associated processes, such as vascular function or cellular senescence and age-associated macular degeneration (Hu et al, 2013;Singh et al, 2014;Eckers et al, 2016;Bravo-Ferrer et al, 2019). The recently generated AhR 3/ 3 mice showed a premature aging phenotype resulting in a reduced life span.…”
Section: Ahr and Aging In Micementioning
confidence: 99%
See 1 more Smart Citation
“…It is discussed that AhR activation induces oxidative stress as a result of excessive generation of ROS. Recent studies indicate that AhR also affects several age-associated processes, such as vascular function or cellular senescence and age-associated macular degeneration (Hu et al, 2013;Singh et al, 2014;Eckers et al, 2016;Bravo-Ferrer et al, 2019). The recently generated AhR 3/ 3 mice showed a premature aging phenotype resulting in a reduced life span.…”
Section: Ahr and Aging In Micementioning
confidence: 99%
“…The recently generated AhR 3/ 3 mice showed a premature aging phenotype resulting in a reduced life span. Those mice display functionality decline in several organs (Fernandez-Salguero et al, 1995;Bravo-Ferrer et al, 2019). In contrast, the AhR 2/ 2 mice show a similar survival rate as wild type mice until 15 months of age and do not display a premature aging phenotype (Singh et al, 2014).…”
Section: Ahr and Aging In Micementioning
confidence: 99%
“…Another study showed that the treatment of mice with three Lactobacillus strains could metabolize tryptophan and alleviate intestinal inflammation through aryl hydrocarbon receptor activation, as the effects were abolished by an aryl hydrocarbon receptor antagonist (Lamas et al, 2016). In addition, aryl hydrocarbon receptor −/− mice showed earlier spatial memory impairment and enhanced astrogliosis in the hippocampus when compared to age-matched aryl hydrocarbon receptor +/+ controls, suggesting a link between aryl hydrocarbon receptor and aging (Bravo-Ferrer et al, 2019). Collectively, the current work and that of others suggested that aryl hydrocarbon receptor could be activated by aryl-containing metabolite during chronic kidney disease progression.…”
Section: Toxicity Of 1-aminopyrene On Nrk-52e Cellsmentioning
confidence: 99%
“…Inactive AhR localizes in the cytoplasm and upon binding of a ligand, the protein dissociates from chaperones and translocates into the nucleus where it binds to nuclear response element and changes gene transcription required for cellular homeostasis [ 6 ]. AhR deficiency accelerates aging in mice and triggers inflammation [ 7 9 ], and AhR ligands play an important role in immune modulation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%